ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN AGRIBISNIS DI BURSA EFEK INDONESIA TAHUN 2007-2012 - Handono, Wahyu; Darta, Effed; Yuliarso, M. Zulkarnain (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2013)
The purpose of this study is to determine the influence of factors of sales growth, tangibility of assets, profitability, liquidity and firm size of capital structure on agribusiness corporates listed on the Indonesia Stock Exchange during 2007-2012. The population used in this study is a company listed on the Indonesia Stock Exchange (BEI) in the period from 2007 to 2012 and is engaged in agribusiness (food crops, plantations, livestock, fisheries, and forestry). The selection of the sample used purposive sampling method. Based on the criteria, 11 companies samples are obtained in the period 2007-2012. The analysis used multiple regression analysis. This research assumed some variables that significantly influence the capital structure (DTA) are the tangibility of assets (FTA), liquidity (CR) and size of company (Size). While the growth in sales (GS) and profitability (NPM) variables had no significant effect on capital structure (DTA). The research result indicates that simultaneous growth in sales (GS), tangibilty of assets (FTA), profitability (NPM), liquidity (CR) and firm size (Size) significantly influence the capital structure (DTA) of the agribusiness company